Building and Maintaining a Citizen Science Network With Fishermen and Fishing Communities Post Deepwater Horizon Oil Disaster Using a CBPR Approach. (November 2018) - Sullivan, John; Croisant, Sharon; Howarth, Marilyn; Rowe, Gilbert T.; Fernando, Harshica; Phillips-Savoy, Amanda; Jackson, Dan; Prochaska, John; Ansari, Ghulam A. S.; Penning, Trevor M.; Elferink, Cornelis; ,
When the Deepwater Horizon oil rig blew out in 2010, the immediate threats to productive deep water and estuarial fisheries and the region's fishing and energy economies were obvious. Less immediately obvious, but equally unsettling, were risks to human health posed by potential damage to the regional food web. This paper describes grassroots and regional efforts by the Gulf Coast Health Alliance: health risks related to the Macondo Spill Fishermen's Citizen Science Network project. Using a community-based participatory research approach and a citizen science structure, the multiyear project measured exposure to petrogenic polycyclic aromatic hydrocarbons, researched the toxicity of these polycyclic aromatic hydrocarbon compounds, and communicated project findings and seafood consumption guidelines throughout the region (coastal Louisiana, Mississippi, and Alabama). Description/analysis focuses primarily on the process of building a network of working fishermen and developing group environmental health literacy competencies.